Pengaruh Locus of Control dan Budaya Organisasi berbasis Tri Hita Karana pada Kinerja Badan Pengawas - Sudiartini, Ni Luh Yuli; Harta Mimba, Ni Putu Sri (E-Jurnal Akuntansi, 2018)
The performance of the supervisory board of a village credit institution (LPD) should be considered because it prevents practices which damage LPD. Good performance of supervisory board of LPD makes the performance increase; therefore the factors that influence it need attention. Individual and situational are the factors can affect the performance of individuals. Individual factors consist of gender, experience, motivation, personality, and locus of control. Meanwhile, situational factors consist of leadership, work achievement, and organizational culture. The aimed of this study was to get empirical evidence regarding the influence of locus control and organization culture based on tri hita karana on the performance of supervisory board of LPD which acts as the internal auditor in Karangasem regency. Tri hita karana is a culture in Bali which develop and appointed into an organization culture which use as a reference in the organization, for example LPD. The data were collected using questionnaire. The sampling method using non probability sampling with purposive sampling technique and 40 samples and 80 respondents were collected. Data were analyzed usingh multipleh linier regressions. The finding of this study showed that the internal locus of control and organizational culture based on tri hitah karana positively impact on the performance of supervisory board of LPD, therefore, when locus of control internal and organization culture based on tri hita karana applied in supervisory board of LPD, the performance was increase. Meanwhile, locus of control external negatively impact on the performance of supervisory board of LPD, therefore, when locus of control external applied in supervisory board of LPD, the performance was decrease. Keywords : Locus of control, organizational culture, tri hita karana, performance